The complete guide to spinning yarn : techniques, projects, and recipes - Gibson, Brenda (Weaver) (St. Martin's Griffin, 2012)
"Whether you are an experienced crafter chasing the perfect yarn or a beginner looking for an outlet for your creative talents, this book will inspire you to get spinning. It starts with the basics and moves through all aspects of spinning until you are producing your own beautiful and functional yarns. Then you can tackle the craft projects at the back of the book using your own unique creations."--P. [4] of cover.